Migratory activation of parasitized dendritic cells by the protozoan Toxoplasma gondii 14‐3‐3 protein. (6th May 2016) - Weidner, Jessica M.; Kanatani, Sachie; Uchtenhagen, Hannes; Varas‐Godoy, Manuel; Schulte, Tim; Engelberg, Klemens; Gubbels, Marc‐Jan; Sun, He Song; Harrison, Rene E.; Achour, Adnane; Barragan, Antonio
Summary: The obligate intracellular parasite Toxoplasma gondii exploits cells of the immune system to disseminate. Upon infection, parasitized dendritic cells (DCs) and microglia exhibit a hypermigratory phenotype in vitro that has been associated with enhancing parasite dissemination in vivo in mice. One unresolved question is how parasites commandeer parasitized cells to achieve systemic dissemination by a 'Trojan‐horse' mechanism. By chromatography and mass spectrometry analyses, we identified an orthologue of the 14‐3‐3 protein family, T. gondii 14‐3‐3 (Tg14‐3‐3), as mediator of DC hypermotility. We demonstrate that parasite‐derived polypeptide fractions enriched for Tg14‐3‐3 or recombinant Tg14‐3‐3 are sufficient to induce the hypermotile phenotype when introduced by protein transfection into murine DCs, human DCs or microglia. Further, gene transfer of Tg14‐3‐3 by lentiviral transduction induced hypermotility in primary human DCs. In parasites expressing Tg14‐3‐3 in a ligand‐regulatable fashion, overexpression of Tg14‐3‐3 was correlated with induction of hypermotility in parasitized DCs. Localization studies in infected DCs identified Tg14‐3‐3 within the parasitophorous vacuolar space and a rapid recruitment of host cell 14‐3‐3 to the parasitophorous vacuole membrane. The present work identifies a determinant role for Tg14‐3‐3 in the induction of the migratory activation of immune cells by T. gondii. Collectively, the findings reveal Tg14‐3‐3 as a novel target for an intracellular pathogen that acts by hijacking the host cell's migratory properties to disseminate.